Synthesis of New Amide and ThioUrease Compounds. (Baghdad Science Journal, 2007)
The reaction of some new Schiff bases ( 2-[(2-Amino – ethylimino)-methyl]-R , 2-({2-[(R-benzylidene)-amino]-ethylimino}-methyl)-R with Benzoyl chloride or Acetyl chloride were carried out. Subsequent reactions of these products N-(2-Amino-ethyl)-N-[Chloro-(R) –methyl]-benzamide or N-(2-{?-[chloro-(R) –methyl]-amino}-ethyl)-N-[chloro-(R) –methyl]- benzamide with thiourea afforded thioureas compounds. The synthesized compounds were confirmed by their IR,UV,spectra and C.H.N. analysis.